CERTIFICATION OF QUALITY CONTROL FOR PERUVIAN AUDIT FIRMS - Urbano Ventocilla, César Maximiliano (2011)
This article aims to present the gap in auditing firms for compliance with Peruvian International Standard on Auditing - ISA, Quality Control in all its dimensions and expose the importance of compliance with it has an international mandate. In Peru, Peruvian Audit Firms operating could be classified into three categories, the leading global ("Big Four"), Medium Firms with international representation and the independent auditors or audit firms with no international representation. All of them are exercising their professional practice and providing service to the local financial community, however can not guarantee that give a quality service, because they do not meet all that the quality standards required by its rules. For example one of the most important reasons that firms do not meet this standard is referred to the high cost they entail. However, as explained in this article for Peruvian audit firms is much more beneficial to their practice, and the cost benefit is fully supported and the high risk that in a globalized world the practice of financial audit could be threatened by investors require in the short term those Audit Firms that do not meet the quality control standards are not eligible as potential providers of this service by closing the doors to their professional practice.